ANALISIS PERAN PERPUSTAKAAN DALAM MENINGKATKAN KETERAMPILAN LITERASI PESERTA DIDIK DI SEKOLAH - Cahyaningtyas, Aura; Arifin, Bustanol; Deviana, Tyas (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
One of Malang's top libraries, Muhammadiyah Elementary School No. 4 Library offers excellent facilities, infrastructure, and a range of literacy-boosting programs. The goal of this study is to determine how Muhammadiyah Elementary School No. 4's library contributes to children' increased literacy in the current digital era. The study's technique was qualitative. To gather information about the study subject and study objects in the field, the researcher employed observation, interviewing, and documenting techniques. The chief librarian and the research documents were the study's topics and objects. The chief librarian's interview served as the major data source, while the results of the observation and documentation research served as the secondary data source. The outcomes of the results of the survey analysis showed that both the volume of books checked out and the number of library visitors are not constant. However, it was discovered through the numerous activities carried out by the library that the function of the library in raising the literacy rate of Malang Muhammadiyah Elementary School fourth grade pupils is entirely doable.